Konsep Garap Tari Pada Karya Tari Ratu Adil - Triyani, Kartina (PPSDP Undergraduate Journal of Educational Sciences, 2025)
A dance work can be formed from the dance artist’s search for ideas through various methods, such as looking at objects around him, observing phenomena that occur in society, reading or listening to stories, legends and so on. which then becomes the basis for the dance artist to create a work. The dance work entitled “Ratu Adil” is a dance work inspired by folklore originating from Lombok, namely Putri Mandalika which tells the story of Putri Mandalika, a female king who succeeded her father. Putri Mandalika is a female figure who is firm in her opinion and is not easily intimidated by anyone in making decisions. The working method uses dramatic and traditional elements. The dance artist tries to explore the ideas obtained into a form of story that can be visualized into forms of movement. From these movements it was then developed into a series of various movements which were divided into each scene. understanding the Ratu Adil dance work. The purpose of this writing is to facilitate understanding of Ratu Adil’s dance work.